NEW METHODOLOGICAL APPROACH TO THE CREATION OF A PERSONALIZED ELIMINATION DIET IN FOOD INTOLERANCE CAUSED BY TYPE III IMMUNOPATHOLOGICAL REACTIONS - M. Yu. Rosensteyn; A. Z. Rosensteyn; S. E. Kondakov; N. A. Cherevko (Бюллетень сибирской медицины)
A new methodological approach to analysis and interpretation of data from a multifaceted analysis ELISA IgG has been provided. The possibility for identification of a “norma-pathology” criterion, on the basis of research yielding a frequency spectrum (or probability density function-PDF) of IgG-immune responses in the integral IgG-immune reply is shown. The possibility for unified diagnostic of hypersensi-tivity type III in patients with varying levels of food disadaptation and symptoms of pathological reac-tions to food antigens is shown too.